PENGARUH STRATEGI THINK-PAIR-SHARE PADA KEMAMPUAN MEMBACA SISWA TAHUN PERTAMA DALAM PEMAHAMAN TEKS DESKRIPTIF DI SMAN 1 TEMPULING - Has, Ria Septiani; Gultom, Effendy; ', Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research is aimed to find out whether there is a significant effect of using think-pair-share in teaching reading descriptive text of the first year students of SMAN 1 Tempuling in the Academic Year 2016/2017 in reading descriptive text. This is a pre-experimental research conducted by using a pre-test – treatment – post-test design. This research used one group pretest-posttest design. The instrument of this research was a reading comprehension test in the form of multiple choices. The population of this research is the first grade students atSMAN 01 Tempuling. There are 161 students in six classes. For the sampling the writer took one class based on the cluster random sampling technique. The collected data were analyzed by using t-test formula. The result of data analysis showed the mean score of pre-test was 65.07 and the mean score of post-test was 67.20. The results of the data analysis illustrates that there are significant effects of using think-pair-share on the students’ reading ability.